Shigella infection in children under 5 years old in western French Guiana. Issue 8 (15th April 2018) - Parisot, M.; Parez, N.; Boukhari, R.; Breurec, S.; Jolivet, A.
Abstract: French Guiana, a tropical country, is characterised by a young and multi-ethnic population. Difficulties in accessing safe water sources lead to outbreaks of gastroenteritis. The objectives of this study were (1) to describe the microbiological profile of shigella strains isolated in western French Guiana, including antimicrobial susceptibility and the distribution of strains in terms of species and serotypes and (2) to estimate the incidence of shigellosis in children under 5 years old. A retrospective observational study was conducted of 213 cases of shigellosis diagnosed in the biology department of the hospital centre for western French Guiana between 2000 and 2012 in children under 5 years old. The serogroups (formerly known as species) that predominates in French Guiana was Shigella flexneri . No resistance was observed to fluoroquinolones or to third-generation cephalosporins. The average incidence of shigellosis in children under 5 years old in western French Guiana was estimated at 189.6 cases per 100 000 inhabitants per year. Shigellosis is a public health problem in western French Guiana. These infections suggest the difficulties in accessing safe water sources and the lack of public sanitation. A quadrivalent vaccine containing Shigella sonnei and three serotypes of S. flexneri ( S. flexneri 2a, 3a and 6) could provide broad coverage against shigella infections.